A case-based review of adult-onset craniopharyngioma - Meyer, Scott; Shah, Shruti N.; Dancel-Manning, Kristen; Wang, Yuxiu; Young, Matthew; Agrawal, Nidhi (Frontiers in Endocrinology, 2025)
Craniopharyngiomas are histologically benign central nervous system tumors derived from embryonic epithelial cells of Rathke’s pouch. The disease demonstrates a bimodal age distribution, occurring most often in patients 5-14 and 50-74 years of age. Common comorbidities include hypopituitarism, hypothalamic obesity, sleep apnea, visual impairment and neurocognitive disturbances. There are several key differences in the presentation, tumor characteristics and clinical outcomes between age groups. Childhood craniopharyngiomas are mostly adamantinomatous and often present as larger tumors with worse functional outcomes such as rates of obesity and neurological deficits. Adults experience similar but slightly adjusted rates of comorbidity with both the adamantinomatous and papillary subtypes. This review presents a case-based discussion of adult craniopharyngiomas, focusing on recent literature regarding their presentation, pathology and pathogenesis, diagnosis, treatment and long-term sequelae.